ÇİNKO OKSİT ARAYÜZEYLİ YARIİLETKEN-YARIİLETKEN UV FOTODEDEKTÖRLER - DEMİRBİLEK, NİHAT (Fırat Üniveristesi, 2019)
Bu tezde katkısız ZnO, farklı oranlarda katkılı ZnO:Alx:My x=%1 at , y=%1, %2, %3, %5 M=Cd, Cu, Mn ince filmler sol jel yöntemi ile hazırlandı. Katkısız ve katkılı ZnO ince filmler döndürerek kaplama (spin coating) metodu kullanılarak cam altlık üzerine oluşturuldu. Hazırlanan katkısız ve katkılı ZnO ince filmlerin yasak enerji band aralığını belirlemek için soğrulma ve geçirgenlik ölçümleri alındı. Filmlerin yapısal özellikleri XRD tekniği ile araştırıldı. XRD sonuçları katkısız ve katkılı ZnO ince filmlerin polikristal yapıya sahip olduğunu doğruladı. Ayrıca ince filmlerin yüzey görüntüleri SEM ile alındı. Hazırlanan katkısız n-Si/ZnO/Al, farklı oranlarda katkılı n-Si/ZnO:Alx:My/Al x=%1 at , y=%1, %2, %3, %5 M=Cd ve p-Si/ZnO:Alx:My/Al x=%1 at , y=%1, %2, %3, %5 M=Cu, Mn foto diyotların optoelektronik karakterizasyonu için gerekli parametrelerin hesaplanabilmesi için diyotların akım-voltaj, kapasite-voltaj, iletkenlik-voltaj ve fotoiletkenlik ölçümleri yapıldı. Diyotların arayüzey özellikleri ve elektriksel parametreleri (Alx

In this thesis, undoped ZnO and (ZnO:Alx:My x=%1 at , y=%1, %2, %3, %5 M=Cd, Cu, Mn) co-doped ZnO thin films were prepared by sol gel method to fabricate the metal oxide semiconductor based photodiodes. Undoped and co-doped ZnO thin films were grown on the glass substrates using spin coating method. The absorbance and transmittance of prepared undoped and co-doped ZnO thin films were measured to determine their optical band gaps. Optical band gaps of undoped and co-doped ZnO thin films were calculated via ?(?hv)?^(1/n) = A(hv-Eg) equation and the results are discussed and correlated with photodiode performance. The structural properties of the thin films were investigated by X-ray diffraction techniques. The XRD results confirm that the undoped ZnO and co-doped ZnO thin films have the polycrystalline nature. For all the thin films, (002) diffraction peaks are observed in the XRD pattern, showing the preferential growth of ZnO crystallites along c-axis. The typical hexagonal wurtzite structure of thin films is inferred from the XRD pattern. Also the surface images of undoped and co-doped ZnO thin films were taken by SEM. It is apparent from the electron micrographs that morphology of all the thin films has tightly packed grains and relatively smooth surfaces without any voids and crack. The electrical characterization of prepared undoped n-Si/ZnO/Al, co-doped n-Si/ZnO:Alx:My/Al x=%1 at, y=%1, %2, %3, %5 M=Cd and co-doped p-Si/ZnO:Alx:My/Al x=%1 at , y=%1, %2, %3, %5 M=Cu, Mn photodiodes were performed by phototransient current measurements, current-voltage characteristics, capacitance-voltage and conductance-voltage techniques. The electrical parameters and interface properties of the photodiodes were changed with (Alx
Zinc oxide interface semiconductor- semiconductor UV photodedectors
Keywords: Fizik ve Fizik Mühendisliği